THE ISSUE OF PEDAGOGICAL PERSONNEL OF UZBEKISTAN IN THE 20S-30S OF THE 20TH CENTURY - Mardiyeva Guzal Karimovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Abstract. In the 20-30s of the 20th century, this article describes the need for pedagogic personnel in the territory of Uzbekistan, the work done on the issue of training new pedagogic personnel. The impact and importance of the ideological policy of the Soviet government on education is also emphasized.